(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
he public federal budget of the state includes estimated figures for state revenues and expenditures for the next fiscal year. The estimation process is one of the main parts of the preparation of the general budget of the state and the accuracy in the estimation of revenues and expenditures of the most important principles that should be based on the process of making estimates and should not overestimate the assessment process to ensure the availability of funds in the future in all cases, which lead to unfair distribution of allocations, so the research aims to study The case of preparing the budget in the Directorate and how to estimate the expenditure in, by the analysis of operating budgets and identify deviations in the implementation of the public budget and the ability of the government unit to correct these deviations. The research find out that the federal budget is prepared for the state on the basis of the level of expenditure in the previous year with the addition of a certain percentage according to personal estimation without depending on the scientific and objective basis we find that the process of preparing the budget from the stage of preparation to the stage of Ratification by Parliament is going through a series of negotiations and dialogues and bargaining, and the deficit that appears in the federal budget of the state is a planning estimated deficit, where the budget is approved with deficit and then moved to a surplus and this indicates to an inaccurate estimates, and the absence of planning with clear goals at the strategic level, medium and short. The research recommends to preparation of estimates of the public federal budget of the state on scientifical, objectival and methodical basis, away from the personal judgment and activating the role of the Committee of preparing the budget in education to apply advanced scientific methods to activate the role of the budget in planning and control, and the need for participation of all parties associated with the budget, both whom prepare the budget or the Beneficiaries, and training of all parties involved in the process of preparing the budget as well as beneficiaries , in order to clarify the scientific and substantive basis in the process of preparing and implementing the budget. key words / public budget, public expenditure.